Post-Translational S-Nitrosylation of Proteins in Regulating Cardiac Oxidative Stress - Xiaomeng Shi; Hongyu Qiu (MDPI AG, 2020)
Like other post-translational modifications (PTMs) of proteins, S-nitrosylation has been considered a key regulatory mechanism of multiple cellular functions in many physiological and disease conditions. Emerging evidence has demonstrated that S-nitrosylation plays a crucial role in regulating redox homeostasis in the stressed heart, leading to discoveries in the mechanisms underlying the pathogenesis of heart diseases and cardiac protection. In this review, we summarize recent studies in understanding the molecular and biological basis of S-nitrosylation, including the formation, spatiotemporal specificity, homeostatic regulation, and association with cellular redox status. We also outline the currently available methods that have been applied to detect S-nitrosylation. Additionally, we synopsize the up-to-date studies of S-nitrosylation in various cardiac diseases in humans and animal models, and we discuss its therapeutic potential in cardiac protection. These pieces of information would bring new insights into understanding the role of S-nitrosylation in cardiac pathogenesis and provide novel avenues for developing novel therapeutic strategies for heart diseases.